Role of Amorphous Calcium Phosphate in Dentistry - Valian, Azam; Moezzyzadeh, Maryam; Moravejsalehi, Elham (Journal of Dental School, 2019)
Objective: Amorphous calcium phosphate (ACP) is a reactive solution capable of releasing calcium and phosphate ions, conversion to apatite and remineralization of mineral tooth structure. This study reviews ACP structure, its properties and its applications in dentistry. Methods: In this review study, keywords including “amorphous calcium phosphate”, “mineralization”, “hydroxyapatite”, “casein phosphopeptide”, “tissue engineering” and “dentistry” were searched in articles published during 1953-2013 in PubMed, Science Direct, Google Scholar, Embase and Medline databases. A total of 134 articles were evaluated. Results: ACP had high adhesion, adjustable dissociation rate, bone induction and excellent biocompatibility without cell toxicity. ACP alone or in combination with casein phosphopeptide (CPP) is incorporated into toothpastes, chewing gums, mouth rinses, tooth bleaching gels and food products to enhance remineralization and prevent demineralization. Also, it is used as filler in many dental materials namely glass ionomers, composite resins and bonding agents. Implant surface coating with ACP by radio frequency magnetron sputtering improves osseointegration especially at the final stages of healing. Conclusion: ACP is suitable for tissue regeneration and healing and is a potential remineralizing agent in dentistry.